Rethinking Legal Practice, and Its Consideration From the Position of Post-Classical Legal Method - I. L. Chestnov (Теоретическая и прикладная юриспруденция)
The article presents the author’s position on the issue of legal practice. Today, a negative phenomenon is being discovered — the isolation of abstract, general concepts of the theory of law from the needs of legal practice. Therefore, accusations by representatives of branch legal sciences of the dogmatism of the theory of law are fully justified. This requires a rethink of legal practice. The most adequate program for clarifying the content of legal practice, in the author’s opinion, is the postclassical methodology. Signification (sign mediation), reflexivity (signification, comprehension and evaluation of the behavioral aspect), discursivity, constructability, contextuality, relativity, human dimension form the content of legal practice in the postclassical dimension. The emphasis of the post-classical research program for the study of legal practice is on the study of legal everyday life. It is formed by legal frameworks and scripts — the framework of informal norms and practices, which are the main regulators of legal behavior. The most promising approach to their study is the method of included observation within the framework of socio-cultural anthropology of law.